PENGARUH IKLAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN YAMAHA MIO - Sembiring, Dessy; Nugraha, Hari Susanta; Prabawani, Bulan (Jurnal Ilmu Administrasi Bisnis, 2014)
Potential national automotive industry makes competition very tight motor vehicle manufacturers. Yamaha Mio is well known that once the automatic sales pioneer matic motorcycle class of the famous. But this time, with more and more competitors of Yamaha Mio automatic resulted in a decrease in sales. Therefore PT. Yamaha Mataram Sakti as large companies in Semarang increasingly reminded to keep attention to the ad and the brand image of products so that consumers increasingly have more confidence to keep using Yamaha Mio.This study aims to determine the effect of advertising and brand image, the decision of buying Yamaha Mio This type of research that is used is an explanation (explanatory research). The sampling technique used was purposive sampling of 100 respondents. Data analysis technique used in this study is a cross table, simple linear regression, multiple linear regression and hypothesis testing.From the research, there is a positive and significant effect between advertising on product purchasing decisions Yamaha Mio, where 9.469 t > t table (1.988) ads influence the buying decision for 47.8%. second; there is a positive and significant effect between brand image on purchase decisions Yamaha Mio which 12,422 t count > t table (1.988) brand image influence on purchase decisions by 61.2%. third; there is a positive and significant effect between advertising and brand image, the decision of buying Yamaha Mio where the calculated F (87.531) > F table (3.09). Taken together advertising and brand image influence purchasing decisions with a coefficient of determination of 64.3%.Based on the research results, PT. Mataram Yamaha Sakti in the city of Semarang strive to create attractive advertising on various media effectively and efficiently and to improve the brand image of Yamaha Mio with a positive impact on purchasing decisions. Because of advertising and brand image influence on purchase decisions Yamaha Mio Suggestions put forward is the need to enhance the brand image through product quality and increase the intensity and frequency of advertising creativity advertising loyalty to the creation of products that can lead to an increase in the purchase decision.